2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin and TGFβ3-Mediated Mouse Embryonic Palatal Mesenchymal Cells. Issue 1 (1st March 2019) - Gao, Liyun; Xu, Jie; Li, Xiao; Wang, Tao; Wu, Weidong; Cao, Jia
2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin (TCDD) is a well-known environmental teratogenic effector for cleft palate. Transforming growth factor 3 ( TGF-β3 ) is an essential growth factor for palatogenesis. The objective of this study is to clarify the effects of TCDD and TGF-β3 in mouse embryonic palatal mesenchymal (MEPM) cells. The effects of 10 nM TCDD, 10 ng/mL TGF-β3, or a combination of 10 nM TCDD and 10 ng/mL TGF-β3 on MEPM cells were revealed by cell and biological methods. With the increase in TCDD (0.5-10 nM), the expression of TGF-β3 increased, but at TCDD concentrations greater than 10 nM, the expression of TGF-β3 reduced. The viabilities of MEPM cells decreased in the 10 nM TCDD-treated group. But the viabilities increased in the 10 ng/mL TGF-β3 -treated group, and the viabilities were intermediate in the group treated with a combination of 10 nM TCDD and 10 ng/mL TGF-β3 . This phenomenon was the same as that of the motilities. In addition, we found that the expression of p-Smad2, p-Smad3, and Smad7 were increased by TCDD, TGF-β3, combination of TCDD and TGF-β3, but the expression of Smad4 were decreased by TCDD, TGF-β3, combination of TCDD and TGF-β3 . These data revealed that TCDD and TGF-β3 interacted and affected MEPM cells.